Overnight/first-morning urine free metanephrines and methoxytyramine for diagnosis of pheochromocytoma and paraganglioma: is this an option?. Issue 5 (May 2020) - Peitzsch, Mirko; Kaden, Denise; Pamporaki, Christina; Langton, Katharina; Constantinescu, Georgiana; Conrad, Catleen; Fliedner, Stephanie; Sinnott, Richard O; Prejbisz, Aleksander; Därr, Roland; Lenders, Jacques W M; Bursztyn, Michael; et al.
Abstract : Objective: Sympathoadrenal activity is decreased during overnight rest. This study assessed whether urinary-free normetanephrine, metanephrine and methoxytyramine in overnight/first-morning urine collections might offer an alternative to measurements in 24-h collections or plasma for diagnosis of pheochromocytoma and paraganglioma (PPGL). Design and methods: Prospective multicenter cross-sectional diagnostic study involving 706 patients tested for PPGL, in whom tumors were confirmed in 79 and excluded in 627 after follow-up. Another 335 age- and sex-matched volunteers were included for reference purposes. Catecholamines and their free O-methylated metabolites were measured in 24-h collections divided according to waking and sleeping hours and normalized to creatinine. Plasma metabolites from blood sampled after supine rest were measured for comparison. Results: Urinary outputs of norepinephrine, normetanephrine, epinephrine and metanephrine in the reference population were respectively 50 (48–52)%, 35 (32–37)%, 76 (74–78)% and 15 (12–17)% lower following overnight than daytime collections. Patients in whom PPGLs were excluded showed 28 (26–30)% and 6 (3–9)% day-to-night falls in normetanephrine and metanephrine, while patients with PPGLs showed no significant day-to-night falls in metabolites. Urinary methoxytyramine was consistently unchanged from day to night. According to receiver-operating characteristic curves, diagnostic accuracy of metabolite measurements in overnight/first-morning urine samples did not differ from measurements in 24-h urine collections, but was lower for both than for plasma. Using optimized reference intervals, diagnostic specificity was higher for overnight than daytime collections at similar sensitivities. Conclusions: Measurements of urinary-free catecholamine metabolites in first-morning/overnight urine collections offer an alternative for diagnosis of PPGL to 24-h collections but remain less accurate than plasma measurements.